Pengaruh Terpaan Pemberitaan Kasus Afif Maulana dan Kredibilitas Media Tempo.co Terhadap Citra Kepolisian RI (Studi Kuantitatif pada Mahasiswa Universitas Sebelas Maret) - Nurhaliza Putri; Adrine Prima Afneta Arzil (Jurnal Komunikasi Massa, 2025)
The rapid advancement of internet technology has facilitated the dissemination of information, particularly through online media, which enables information to reach a broad audience quickly. One of the credible online media platforms in Indonesia is Tempo.co, which actively reports on various sensitive cases, including the Afif Maulana case. This case involves allegations of abuse by police officers and has drawn public attention for tarnishing the image of the Indonesian National Police (Polri). This study was conducted to analyze the influence of news exposure regarding the Afif Maulana case on Tempo.co and the credibility of the media on the image of Polri, particularly among students of Universitas Sebelas Maret. The research employed a quantitative explanatory method by distributing questionnaires to 99 Universitas Sebelas Maret students aged 18-25 years who had read news related to the case. The sample was selected using an accidental sampling technique. The theoretical framework included the Stimulus-Organism-Response (S-O-R) Theory, Source Credibility Theory, and Uses and Effects Theory. The results of the study indicate that the credibility of Tempo.co has a significant positive influence on the image of Polri. This finding underscores the importance of public trust in the media in shaping their perceptions of public institutions. In contrast, news exposure alone did not show a significant influence on Polri's image when analyzed partially. However, when analyzed simultaneously with media credibility, news exposure demonstrated a significant influence on Polri's image.